2022
DOI: 10.1111/1440-1681.13631
|View full text |Cite
|
Sign up to set email alerts
|

Association between anti‐fibrillin‐2 protein induced retinal degeneration via intravitreous delivery and activated TGF‐β signalling in mice

Abstract: Fibrillin‐2 (FBN2) is a major component of tissue microfibrils, and the decrease of FBN2 perturbs the signalling events mediated by transforming growth factor‐β (TGF‐β), thereby playing a role in macular degeneration. However, the association between the retinal degeneration resulting from the abnormality of FBN2 and the activation of TGF‐β signalling has not been fully addressed. In the present study, the mice were divided into a normal control group (NC group), a phosphate‐buffered saline (PBS) injection gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…A non-synonymous variant of the FBN2 gene, rs154001 (p.Val965Ile), was identified to be associated with AMD, and the non-synonymous variants of the FBN2 gene, including c.3430G-A (p. Glu1144Lys), c.3740T-C(p.Met1247Thr), c.4312G > A(p.Glu1438Lys) and c.4141C > A (p.His1381Asn) were identified in patients with EOMD 1 . It has been reported that the FBN2 protein is located in Bruch's membrane, that it is reduced in AMD eyes, and that a reduction in the expression of fbn2 in the retina was associated with the development of a retinopathy in mice 1 , 7 . Recombinant proteins have been considered to be therapeutic agents for the treatment of inherited diseases, however, their clinical application has been limited due to their inability to enter the targeted cells and to be functional in the intracellular site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A non-synonymous variant of the FBN2 gene, rs154001 (p.Val965Ile), was identified to be associated with AMD, and the non-synonymous variants of the FBN2 gene, including c.3430G-A (p. Glu1144Lys), c.3740T-C(p.Met1247Thr), c.4312G > A(p.Glu1438Lys) and c.4141C > A (p.His1381Asn) were identified in patients with EOMD 1 . It has been reported that the FBN2 protein is located in Bruch's membrane, that it is reduced in AMD eyes, and that a reduction in the expression of fbn2 in the retina was associated with the development of a retinopathy in mice 1 , 7 . Recombinant proteins have been considered to be therapeutic agents for the treatment of inherited diseases, however, their clinical application has been limited due to their inability to enter the targeted cells and to be functional in the intracellular site.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental study included adult C57BL/6J male mice with an age of 8 weeks and a body weight of 22–23 g (supplied by Beijing Vital River Experimental Animal Technology Co. Ltd., Beijing, China.) 7 . The Ethics committee of the Eye Institute of the Shandong University of Traditional Chinese Medicine approved the study and confirmed that its design was in accordance with ARVO (Association for Vision and Eye Research) statement for the use of Ophthalmic and Visual Research.…”
Section: Methodsmentioning
confidence: 99%